Frontal Analysis Continuous Capillary Electrophoresis Study on the Interaction of an Amphiphilic Alternating Copolymer with Triton X-100 - Akihito Hashidzume; Takuya Shimomachi; Takahiro Sato (International Journal of Analytical Chemistry)
The interaction of amphiphilic alternating copolymers of sodium maleate and dodecyl vinyl ether (Mal/C12) with a nonionic surfactant, Triton X-100 (TX), was investigated by frontal analysis continuous capillary electrophoresis (FACCE). The binding isotherms obtained from FACCE data were indicative of weak cooperative interaction for all the polymers examined. The cooperative interaction was also analyzed by the Hill model, and the results were compared with the previous results on the interaction of statistical copolymers of sodium 2-acrylamido-2-methylpropanesulfonate and N-dodecylmethacrylamide with TX.